Comparative analysis of post-operative analgesic requirements in patients undergoing minor oral surgery using buprenorphine with lignocaine versus lignocaine: a clinical study - Kamal, Neel; Sheikh, Alfisha; Alwyn, Vaz Ashwin; Kaur, Navneet; Shekhar, Chandra; Sharma, Amit (International Journal of Research in Medical Sciences, 2022)
Background: We aimed to inspect the post -operative analgesic requirement in patient undergoing minor oral surgery using buprenorphine versus lignocaine and lignocaine alone. Minor oral surgeries are followed by inflammatory reaction characterized by pain, mild swelling and discomfort. Opioid analgesics have an advantage over non-steroidal anti-inflammatory drugs (NSAIDs) as they do not cause organ damage. Buprenorphine has an antinociceptive potency greater than that of morphine. Hence, in this study, buprenorphine was added to lignocaine in relieving postoperative pain after minor oral surgery. Methods: A total of 100 patients requiring minor oral surgery were included in the study. The patients were randomized by a third party and allocated to one of the two study groups. Hence a total of 50 patients in each group were selected for study, during a period of 24 months. 1 ml of buprenorphine hydrochloride injection I.P which contains an equivalent of 0.3 mg buprenorphine was withdrawn into a syringe and injected into a 30 ml vial of 2% lignocaine with adrenaline 1:200000. Results: The pain was found to be statistically significant at 2-hour, 24 hour and 36 hours postoperatively, thereafter the difference in NRS values between the solutions was not significant. Hence, the analgesic effect of solution A (buprenorphine) was effective at 2-hour, 24 hour and 36 hours postoperatively. Conclusions: Our study indicate that addition of 0.3 mg of buprenorphine to local anesthetic solution provides efficient post-operative analgesia and reduces patient’s discomfort.